THE INFLUENCE OF REVOLUTION IN MILITARY AFFAIRS ON INDONESIAN DEFENSE FORCES IN THE SOUTHEAST ASIAN REGION - Santoso, Rachmat Yudi (Jurnal Analisis Sosial Politik, 2021)
The development of Indonesia's defense capability currently has an influence on the quality and quantity in the use of military technology. The role of the Indonesian government as the main actor driving military technology is one of the important instruments in advancing the Indonesian defense forces. The influence of Revolution in Military Affairs for Indonesian defense forces has a relationship with the Minimum Essential Force conducted in the third stage of 2020-2024 so that this basis becomes crucial for increasing Indonesia's defense capability. This research also looks at security issues that occur in the Southeast Asian region so that the increase in defense capability has a cause for the development of security issues that occur. Indonesian defense forces are not merely carried out as a form of Indonesian defense doctrine. But as an effort to achieve national security and interests. This study uses a qualitative research method with analytic descriptive so that it not only explains the problems that occur but also analyzes the problems that occur. The researcher found the fact that Indonesia is not only serious in increasing defense power. In 2020, Indonesia will improve and prioritize defense as the main sector in the government budget. Thus, it shows the government's seriousness in carrying out strengthening of the country's power base. The author also analyzed the security issues in the Southeast Asian region so that readers know the problems and causes of Indonesia to improve defense capabilities.